The struggle for Jerusalem and the Holy Land : a new inquiry into the Quran and classic Islamic sources on the people of Israel, their Torah, and their links to the Holy Land - Dana, Nissim, 1938- (Israel (Boston, Mass.), 2014)
In recent generations, the Muslim and Arab world has been suffused with publications on the subject of the People of Israel, its Torah, and this people's affinity to the Land of Israel. Most of these publications are tendentious, written with a hostile attitude toward Jews and Judaism; indeed, some of them are tainted with antisemitism. The Qur'an, the Holy Scripture of the Muslims, also deals with the question of the status of Eretz Israel, the Land of Israel. Many of its exegetes, following in the tracks of Islam's holy book, have done so as well. Somewhat surprisingly, perhaps, these Islamic sources express an approach asserting that this land is promised exclusively to the People of Israel. This book explores these sources and discusses them in light of the recent developments.